Epidemiological Determinants of Advanced Prostate Cancer in Elderly Men in the United States - Jayasekera, Jinani; Onukwugha, Eberechukwu; Cadham, Christopher; Tom, Sarah; Harrington, Donna; Naslund, Michael (Clinical Medicine Insights. Oncology, 2019)
In this study, we examined the effects of individual-level and area-level characteristics on advanced prostate cancer diagnosis among Medicare eligible older men (ages 70+ years). We analyzed patients from the linked Surveillance, Epidemiology, and End Results (SEER)-Medicare database (2000-2007) linked to US Census and County Business Patterns data. Cluster-adjusted logistic regression models were used to quantify the effects of individual preventive health behavior, clinical and demographic characteristics, area-level health services supply, and socioeconomic characteristics on stage at diagnosis. The fully adjusted model was used to estimate county-specific effects and predicted probabilities of advanced prostate cancer. In the adjusted analyses, low intensity of annual prostate-specific antigen (PSA) testing and other preventive health behavior, high comorbidity, African American race, and lower county socioeconomic and health services supply characteristics were statistically significantly associated with a higher likelihood of distant prostate cancer diagnosis. The fully adjusted predicted proportions of advanced prostate cancer diagnosis across 158 counties ranged from 3% to 15% (mean: 6%, SD: 7%). County-level socioeconomic and health services supply characteristics, individual-level preventive health behavior, demographic and clinical characteristics are determinants of advanced stage prostate cancer diagnosis among older Medicare beneficiaries; other health care-related factors such as family history, lifestyle choices, and health-seeking behavior should also be considered as explanatory factors.